2010
DOI: 10.4049/jimmunol.1001564
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Complement Mannose-Binding Lectin-Associated Serine Proteases-1/3 in the Murine Collagen Antibody-Induced Model of Inflammatory Arthritis

Abstract: Gene-targeted mice deficient in the complement mannose-binding lectin-associated serine protease-1 and -3 (MASP1/3−/−) express only the zymogen of factor D (pro-factor D [pro-Df]), a necessary component of the alternative pathway (AP). We used the murine collagen Ab-induced arthritis (CAIA) model, in which the AP is unique among complement pathways in being both necessary and sufficient for disease induction, to determine whether MASP-1/3 are required in vivo for the development of tissue injury. Disease activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 41 publications
10
71
2
Order By: Relevance
“…CAIA was induced in WT mice using a cocktail of 5 mAbs to bovine CII (Arthritomab-CIA, Chondrex) suspended in sterile PBS as previously described (4, 17, 38). WT mice were injected i.p.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CAIA was induced in WT mice using a cocktail of 5 mAbs to bovine CII (Arthritomab-CIA, Chondrex) suspended in sterile PBS as previously described (4, 17, 38). WT mice were injected i.p.…”
Section: Methodsmentioning
confidence: 99%
“…S2A). Clinical disease activity (CDA) was examined daily until day 10 by observers blinded to the treatment as per our previously published studies (4, 17, 38). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since MASP-1 and MASP-3 are crucial for AP activation via FD activation, it was examined whether the expression of MASP-1/3 is essential for the development of CAIA (Banda et al, 2010). In the report, it was shown that Masp1/3 −/− mice are highly resistant to CAIA as evidenced by a significant decrease compared to WT mice (Banda et al, 2010). This evidence strongly supports that MASP-1 and MASP-3 are required for the AP activation in vivo.…”
Section: Collagen Antibody Induced Arthritis (Caia) Model In Mousementioning
confidence: 99%
“…MASP1 is also able to cleave C3 directly, which results in activation of the alternative pathway (27). Others, based on a knockout mouse model, have also proposed a role for MASP1 and MASP3 in directly activating the alternative pathway factor D as well as limited factor B cleavage by MASP3 (28)(29)(30). However, there are ongoing debates on these findings (31,32).…”
Section: The Lectin Pathwaymentioning
confidence: 95%